To Examine the Processes of Biochemical Action Of 6-Benzylaminopurine with Cobalt-II Nitrate Dihydrate on the “Morus Alba” Variety of Moraceae Plant - G.O. Boymuratova; F.E. Saitkulov; Kh.M. Nasimov; J. G’.Rahimov; M.Tugalov (Genius Journals, 2022)
The effects of the reaction of coordination compounds of cobalt II nitrate with 6- benzylaminopurine on the “morus alba” variety of moraceae plant were studied. 6- Benzylaminopurine is a broad-spectrum plant growth regulator, capable of rejuvenating plants, bringing plants out of dormancy, causing the formation of lateral shoots and root shoots
Keywords: The effect; reaction of coordination; cobalt II-nitrat; moraceae plant